Peran Indeks Pembangunan Manusia (IPM) Dalam Memutus Rantai Kemiskinan Dan Ketimpangan Pendapatan Di Kabupaten Probolinggo - Farah Sabilatul Jannah; Holifah; Musrifa (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to analyze the effect of Human Development Index (HDI) dimensions, such as health, education, and per capita expenditure, on poverty levels and income inequality (Gini Index) in Probolinggo Regency. Although regional economic development in 2020-2024 shows a positive trend, with the HDI of Probolinggo Regency increasing by an average of 0.75%, the issues of poverty and income inequality remain major challenges. Limited access to education and health services in some areas has resulted in low productivity and increased economic inequality. This study utilizes a descriptive quantitative approach to analyze the influence of each HDI dimension on poverty and the Gini Index. The results of this study are expected to serve as a reference for local governments in formulating more efficient and sustainable development policies to reduce poverty and promote economic equality in Probolinggo Regency.